Effect of the supplementation of olive leaves and olive cake on growth performance and bone mineralisation of broiler chickens - Manca Pečjak (Acta Fytotechnica et Zootechnica, 2020)
The by-products of olive oil production are not traditional feed ingredients in poultry nutrition. Despite their low nutritional value, they can be used not only as a source of energy and nutrients, but also as bioactive substances in nutrition of broiler chickens. The aim of the study was to determine whether the use of olive leaves and cake in feed mixtures for broilers affects their growth performance and bone mineralisation. In the feeding experiment 120 male Ross 308 broilers were used. At the age of 21 days the chickens were randomly assigned to 5 experimental groups each with two pens (replicates) of 12 animals and fed with 5 different feed mixtures without (Control) or supplemented with 5% or 10% olive leaves (OLeave5, OLeave10) or cake (OCake5, OCake10). Live weight and feed intake per pen were recorded weekly. At the end of the feeding experiment (42 days), 12 chickens per group were randomly selected and slaughtered. At the slaughter line, bone samples (femur, tibia and humerus) were taken from each chicken. The supplementation of olive leaves and cake had no significant effect on the growth performance and mineral content in femur, tibia and humerus of the broilers. The addition of 5 and 10% olive leaves to the feed resulted in higher Cu content in the humerus, but bone mineralisation did not change. In conclusion olive leaves and cake did not modify bone mineralisation but could be supplemented in the feed mixtures for broilers without negative effects on growth performance.